Genetic diversity and conservation of Carex kobomugi in Taiwan - Chi-Chun HUANG; Chao-Yu HSU; Kuo-Hsiang HUNG; Tsai-Wen HSU; Chau-Ching HUANG; Munkhtsetseg TSEDNEE; Chuan-Ming YEH; Wei-Kuang WANG (TAIWANIA, 2025)
Carex kobomugi is native to the coastal sand dunes and sandy beaches of East Asia, including China, Japan, Korea, Taiwan, and the Russian Far East. In Taiwan, C. kobomugi, which is categorized as threatened species (category of critically endangered, CR), is narrowly distributed in northern Taiwan and offshore islands. First recorded in 1924, the species disappeared for a time but was rediscovered in 2020. However, it is currently threatened by increasing human activities and faces the risk of local extinction. In this study, we employed molecular markers (rpL16 spacer of cpDNA, ITS region of nrDNA and eleven microsatellite loci) to evaluate the genetic diversity and population structure. The results showed that the low genetic diversity of C. kobomugi in Taiwan may be attributed to small population size, and geographic isolation based on cpDNA and nrDNA. In contrast to the identical nrDNA sequences across different regions, a unique cpDNA haplotype identified exclusively in Taiwan underscores the need for focused conservation efforts. A moderate level of genetic diversity was found for microsatellite loci, and STRUCTURE and principal coordinates analysis revealed that the two genetic groups corresponded to their geographical distributions. Based on these findings, two distinct management units are recommended for further conservation. Actions such as manually conducted beach cleanups, species inventories, and both in-situ and ex-situ conservation have been implemented to mitigate human disturbance.